(untitled) (Educational Knowledge, 2023)
Parents play a crucial role in their children’s education, initially providing guidance in the family environment and later sharing educational responsibilities with schools. The relationship between these two spheres and the communication channels established between them are of utmost importance. This article conceptually approaches family engagement, describing the essential elements necessary for its implementation—namely, the willingness, capability, and knowledge to participate. It also delves into levels of engagement, particularly Epstein’s (2011) classification, emphasizing the synergistic interaction between family and school environments.